Neurostimulation for Neurogenic Bowel Dysfunction. (21st March 2013) - Worsøe, J.; Rasmussen, M.; Christensen, P.; Krogh, K.
Abstract : Background . Loss of normal bowel function caused by nerve injury, neurological disease or congenital defects of the nervous system is termed neurogenic bowel dysfunction (NBD). It usually includes combinations of fecal incontinence, constipation, abdominal pain and bloating. When standard treatment of NBD fails surgical procedures are often needed. Neurostimulation has also been investigated, but no consensus exists about efficacy or clinical use. Methods . A systematic literature search of NBD treated by sacral anterior root stimulation (SARS), sacral nerve stimulation (SNS), peripheral nerve stimulation, magnetic stimulation, and nerve re-routing was made in Pubmed, Embase, Scopus, and the Cochrane Library. Results . SARS improves bowel function in some patients with complete spinal cord injury (SCI). Nerve re-routing is claimed to facilitate defecation through mechanical stimulation of dermatomes in patients with complete or incomplete SCI or myelomeningocele. SNS can reduce NBD in selected patients with a variety of incomplete neurological lesions. Peripheral stimulation using electrical stimulation or magnetic stimulation may represent non-invasive alternatives. Conclusion . Numerous methods of neurostimulation to treat NBD have been investigated in pilot studies or retrospective studies. Therefore, larger controlled trials with well-defined inclusion criteria and endpoints are recommended before widespread clinical use of neurostimulation against NBD.